Electrochemical faceting of polycrystalline gold in 1 M H2SO4 - Perdriel, Carlos L. (1986)
Electrochemical faceting of polycrystalline (pc) gold electrodes in 1 M H2SO4 was investigated by employing wire and bead-shaped electrodes. Electrochemical faceting was produced by applying a repetitive symmetrical square wave potential signal in the 2–4 kHz range and upper and lower potential limits ranging between 1.44 and 1.60 V (vs. RHE) and 0.10 and 1.10 V, respectively. The degree of faceting was followed voltammetrically principally through the O-electroadsorption/electrodesorption process. Electrochemical information was complemented with scanning electron microscopic observations. The results are discussed in terms of the equilibrium potential of reactions involving different gold species, and the potential of zero charge, hydrophobicity and anion adsorbability of the (110), (100) and (111) crystallographic faces of gold. The kinetics of electrochemical faceting of gold can be explained through the two-stage mechanism proposed earlier for polycrystalline platinum in acid electrolyte.